Water Rights Dilemma in Indonesia: Coase Theorem and Game Theory Approach - Andar Ristabet Hesda Hesda (Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: This paper aims to explain Indonesia's water rights dilemma and propose a potential solution to solve it using the Coasian and game theory approaches. Background Problems: Developing a mechanism that supports the citizens (and farmers) in the area surrounding water plants, maintains firm productivity, builds social cohesion, and promotes environmental improvement remains an ongoing concern. Novelty: This study utilizes the Coasian and game theory approaches to solve Indonesia's water rights dilemma. Research Methods: This research employs a game theory simulation representing the Coasian strategy in handling externalities. Findings/Results: The implementation of Coasian bargaining might be promising in solving the water rights dilemma in Indonesia. The necessary condition is high farmer commitment during the bargaining process, and the sufficient condition is a reduction of transaction costs. Conclusion: The strategies in lowering transaction costs can be accomplished by establishing an independent multidisciplinary research team, involving a government element as a mediatory body, and creating an advisory firm. This research team would aim to close the gap in institutional deficiency. The government would have a significant role in reducing the transaction cost by defining, enforcing, and transferring property rights. Lastly, the advisory firm would help to focus all business activities, operationalize agreements, and conduct monitoring.